(untitled) (Research, Society and Development, 2023)
Traditional and Complementary Medicine has for decades been stimulated by the World Health Organization in its member countries with the collective interest of stimulating health practices that can go beyond the existing conventional ones. In Brazil, Integrative and Complementary Health Practices (ICHPs) are widely recognized and serve as allied treatments to those of conventional medicine in a predominant biomedical system. With lack of resources, difficult access to health services, and an aging population, integrative therapies such as Phytoenergetics and Phytotherapy need to be considered. Phytoenergetics is a natural healing system that uses the energetic power of plants to balance the body and maintain health. The study developed in the Gerontology Post-Graduation Program at the Federal University of Santa Maria/RS aimed to conduct a theoretical study on the Phytoenergetic technique, from its creator Bruno Gimenes, and to reflect on the importance of combining integrative and complementary practices in health care for the elderly. In conclusion, further study of the use of plants and a deepening of the perceptions of the treatments for the elderly with discussion of relevant results for Gerontology is necessary.